Improving access to livestock markets for sustainable rRangeland management - Evelyne Nyathira Kihiu; Franklin Amuakwa-Mensah (University of Bonn, Center for Development Research (ZEF), 2016)
Productivity of rangelands in Kenya is affected by increasing crop farming especially in more fertile range areas. Among the key factors driving the encroachment of crops on rangelands are the changing opportunities brought about by markets. We hypothesize that the existing market inefficiencies characterizing livestock markets, especially the price disincentives that livestock producers face, are major risks rangelands face. To analyze the effect of livestock market conditions on rangeland management, we draw on household survey and economic modeling tools. We find that traders' rent seeking behavior and high transport costs act as disincentives to livestock producers' participation in livestock markets and influence their decisions in seeking alternative rangeland uses to sustain livelihoods. However, improved livestock market access enhances livestock producers' livelihoods and the stewardship of the ecosystems thus reducing pastoralists' vulnerability to ecological climate variability associated with rangelands.
Keywords: Q13; Q15; Q24; 330; Extensive livestock production; market access; ecological-economic model; positive mathematical programming (PMP) model; Kenya